2014
DOI: 10.1111/apha.12214
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body fluid distribution in humans during dehydration and recovery, before and after humid-heat acclimation induced using controlled hyperthermia

Abstract: It is concluded that the plasma volume was not defended more vigorously following humid-heat acclimation. Indeed, a greater fluid loss may well underlie the mechanisms for enhancing plasma volume recovery when heat acclimation is induced using the controlled-hyperthermia technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 55 publications
2
53
0
Order By: Relevance
“…In this state, and depending upon the ambient conditions, heat storage can approximate heat production , imposing a significant impediment to viable work durations (McLellan et al 2013;Taylor 2015;Taylor and Patterson 2016). Moreover, continued physiological attempts to lose heat can actually exacerbate the problem, with excessive sweating leading to rapid dehydration, and the depletion of body fluids and electrolytes (Patterson et al 2014), whilst cutaneous vascular engorgement (Rowell et al 1970;Fogarty et al 2004) can challenge blood pressure regulation (Taylor and Patterson 2016).…”
Section: Thermoregulatory Consequencesmentioning
confidence: 99%
“…In this state, and depending upon the ambient conditions, heat storage can approximate heat production , imposing a significant impediment to viable work durations (McLellan et al 2013;Taylor 2015;Taylor and Patterson 2016). Moreover, continued physiological attempts to lose heat can actually exacerbate the problem, with excessive sweating leading to rapid dehydration, and the depletion of body fluids and electrolytes (Patterson et al 2014), whilst cutaneous vascular engorgement (Rowell et al 1970;Fogarty et al 2004) can challenge blood pressure regulation (Taylor and Patterson 2016).…”
Section: Thermoregulatory Consequencesmentioning
confidence: 99%
“…Isothermic heat acclimation (also known as controlled hyperthermia) is imposed based upon endogenous (internal) criteria (Castle et al, 2012;Garrett et al, 2014Garrett et al, , 2012Garrett et al, , 2009Hom et al, 2012;Machado-Moreira et al, 2006;Magalhães et al, 2010aMagalhães et al, , 2010bPatterson et al, 2014Patterson et al, , 2004, and might provide sustained targeting and attainment of specific and individualised internal temperatures through a combination of active and passive heat acclimation (Fox et al, 1963). The balance between work and rest to target and maintain specific core temperatures ensures a consistency, or a progression of endogenous heat strain to induce adaptation, albeit requiring alterations in administration throughout each session.…”
Section: Introductionmentioning
confidence: 99%
“…Hypovolemia and hyperosmolality due to thermal dehydration also suppress thermoregulatory responses of sweating and cutaneous vasodilation, resulting in increased risk of heat illness (18). It has been often observed that non-acclimatized individuals tend to consume inadequate fluid leading to hypohydration, which can quickly result in dehydration with increased risk of heat illness / injury (27). Heat acclimatization induced effective adaptations are more pronounced after fluid-regulatory strain from permissive dehydration (11).…”
Section: Research Articlementioning
confidence: 99%
“…It was further observed by Patterson et al that plasma volume was not defended more vigorously following humid-heat acclimatization. Rather a greater fluid loss may well underlie the mechanisms for enhancing plasma volume recovery when heat acclimation is induced using controlled-hyperthermia (26,27). Sufficient body water is required to sustain thermoregulatory function, thus losses in total body water can challenge the thermoregulatory system (18).…”
Section: Research Articlementioning
confidence: 99%